Effect of hygrothermal environment on composite bonded joint - Intan Ruzaini Binti Ahmad (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The objective of this project is to identify the effect of varying hygrothermal environment of composite bonds joint in real working area. Two numbers of physical tests were conducted on carbon and glass fiber prepregs which include resin content test and gel time test. The mechanical test is conducted also to the both materials which is tensile test. Both materials were placed in three different locations with hygrothermal control and without hygrothermal control. The physical properties for both materials in location with humidity and temperature control stay constant and steady after 36 hours. However, the third location without temperature and humidity control affects the material to be out of specification.